Influence of amoxicillin after pre-treatment on the extracellular polymeric substances and microbial community of anaerobic granular sludge. (March 2019) - Su, Chengyuan; Zheng, Peng; Lin, Xumeng; Chen, Wuyang; Li, Xinjun; Chen, Qiuyu; Wu, Shumin; Chen, Menglin
Graphical abstract: Highlights: Degradation pathway of amoxicillin by heterogeneous Fenton-like was proposed. Heterogeneous Fenton-like oxidation of amoxicillin reduced the toxicity. Methanothrix increased and Methanobacterium reduced with heterogeneous Fenton-like pretreatment. Abstract: A combined process coupling a Fe3 O4 nanoparticles (Fe3 O4 NPs) heterogeneous Fenton-like reaction and an anaerobic biological technology was investigated in order to effectively treat amoxicillin-containing wastewater. With the increase in the pretreatment degree, the average COD removal rate correspondingly increased from 84.8% to 92.4% using the anaerobic biological treatment, and the biodegradability and COD removal efficiency was improved by the pretreatment processes. During the process of amoxicillin degradation, hydroxyl free radicals tended to attack the lactamide, amide and pentacyclic rings of amoxicillin. In the excitation-emission matrix (EEM) spectra of soluble microbial products (SMPs), the absorption peak of humic acid gradually decreased with application of the pretreatment. The pretreatment products were more beneficial to the characteristics of anaerobic granular sludge. For the microbial community structure, the proportion of Methanothrix and Clostridia increased with addition the heterogeneous Fenton-like pretreatment, which favored conversion of organic contaminants to volatile fatty acids and biogas.